2004
DOI: 10.1063/1.1756223
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of crystallization of oxygen-doped amorphous Ge1Sb2Te4 thin films

Abstract: The aim of this article is to study the mechanism of the amorphous-to-crystalline phase transformation in Ge1Sb2Te4 alloys doped by oxygen (in the range of 4–28 at. %) using the electrical, optical, and x-ray measurements. Experimental results have shown that samples with oxygen in the range of about 4–10 at. % first crystallize into the Ge1Sb2Te4 fcc phase at temperatures in the range 130–145 °C, at higher temperature (around 275 °C) the fcc phase is transformed into the Ge1Sb2Te4 hexagonal phase. In samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…However, transmittance measurements or other techniques [26][27][28][29][30][31][32][33] generally used, such as differential scanning calorimetry, x-ray diffraction, electrical ͑resistance͒ measurements, and reflectance measurements, provide information only on the overall crystallization process, that is actually an interplay of both nucleation and growth processes. In contrast, transmission electron microscopy ͑TEM͒ is capable of providing separate information on nucleation and growth parameters.…”
Section: Influence Of Capping Layers On the Crystallization Of Doped mentioning
confidence: 99%
“…However, transmittance measurements or other techniques [26][27][28][29][30][31][32][33] generally used, such as differential scanning calorimetry, x-ray diffraction, electrical ͑resistance͒ measurements, and reflectance measurements, provide information only on the overall crystallization process, that is actually an interplay of both nucleation and growth processes. In contrast, transmission electron microscopy ͑TEM͒ is capable of providing separate information on nucleation and growth parameters.…”
Section: Influence Of Capping Layers On the Crystallization Of Doped mentioning
confidence: 99%
“…In addition, previous results have shown that, in amorphous Ge:Sb:Te:O films, with oxygen concentration lower than 10 at.%, the temperature of crystallization, the crystal grain size and the lattice parameters increased with increasing oxygen concentration in [1,3,5,7]. On the other hand, the temperature of crystallization in Ge:Sb: Te:O films with oxygen content above 10 at.% decreases and the material crystallizes into the rhombohedral Sb 2 Te 3 phase [7].…”
Section: Introductionmentioning
confidence: 90%
“…In previous reports, three scenarios of how oxygen incorporates into the Ge:Sb:Te structure have been reported [1,3,5,7]. One of them proposes that oxygen is located at the tetrahedral interstitial site of the Ge:Sb:Te structure [3,5,7].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, several mechanisms have been proposed in respect to oxygen addition. One of them suggested that oxygen incorporation in GST leads to the formation of germanium oxide and phase separation [19]. Other authors claim that formation of stoichiometric GeO 2 phase is not observed, while stoichiometric Sb 2 O 3 phase is formed instead [20].…”
Section: Introductionmentioning
confidence: 97%